De certains aspects de la juridiction de la Régie des services publics en matière de droit municipal - Barbe, Raoul-P. (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
This paper presents a study as of July 1977, of statutory provisions, regulations and decisions which relate to the jurisdiction of the Quebec Public Service Board (Régie des services publics) and the law of municipal corporations in the field of public utilities. Among the topics covered are the following: the amendment of zoning by-laws prescribing the joint use of facilities by public utilities; disputes that arise when public utilities are required to use underground facilities; the role of municipal corporations in the provision of public utility services; and disputes between municipal corporations and public utilities.